2015
DOI: 10.12968/bjon.2015.24.10.536
|View full text |Cite
|
Sign up to set email alerts
|

Noise at night in hospital general wards: a mapping of the literature

Abstract: English NHS inpatient surveys consistently identify that noise at night in hospitals and its impact on patients' sleep is a persisting problem that needs addressing. To identify how noise at night in hospital affects patients on general wards and the range of interventions aimed at reducing the problem, a systematic mapping of the literature was undertaken. All primary studies and relevant literature published January 2003-July 2013 were included. Key issues identified in the literature included noise levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
3
21
1
1
Order By: Relevance
“…7 Previous studies on hospital environment and sleep have focused on noise as the primary disrupter to inpatient sleep. 2,8 For example, Buxton et al performed a laboratory-based study to assess the relationship between hospital noise and sleep physiology and found that noise caused a significant increase in heart rate during sleep. 9 In addition, prior work by our group…”
Section: Introductionmentioning
confidence: 99%
“…7 Previous studies on hospital environment and sleep have focused on noise as the primary disrupter to inpatient sleep. 2,8 For example, Buxton et al performed a laboratory-based study to assess the relationship between hospital noise and sleep physiology and found that noise caused a significant increase in heart rate during sleep. 9 In addition, prior work by our group…”
Section: Introductionmentioning
confidence: 99%
“…The noise is also kept in mind in the dimension “environment”, and it has been described as one important factor influencing comfort. This particular noise not only comes from machinery but also comes from the staff (Buxton et al, ; Fillary et al, ). Another relevant variable influencing comfort is the way that health professionals treat the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Their presence is invasive and results in a chain of physiological events that lead to cortical activation, with vasoconstriction, increased blood pressure, mydriasis, and a greater muscle tension, associated with a sympathetic discharge with adrenaline release. 17 I n g e n e r a l , n o i s e e x c e e d s t h e v a l u e s recommended by the World Health Organization (25-30 decibels), although acoustics levels are unknown because they are not usually measured. Friedman did a polysomnography in 22 patients for 24-48 hours and found that 17 % of arousals and microarousals were caused by noise.…”
Section: The Hospital Settingmentioning
confidence: 99%